Treatment of Systemic Necrotizing Vasculitides in Patients Aged Sixty‐Five Years or Older: Results of a Multicenter, Open‐Label, Randomized Controlled Trial of Corticosteroid and Cyclophosphamide–Based Induction Therapy1. Issue 4 (April 2015) - Pagnoux, Christian; Quéméneur, Thomas; Ninet, Jacques; Diot, Elisabeth; Kyndt, Xavier; de Wazières, Benoît; Reny, Jean‐Luc; Puéchal, Xavier; le Berruyer, Pierre‐Yves; Lidove, Olivier; Vanhille, Philippe; Godmer, Pascal; et al.
Abstract : Objective: To investigate a new therapeutic strategy, with rapid corticosteroid dose tapering and limited cyclophosphamide (CYC) exposure, for older patients with systemic necrotizing vasculitides (SNVs; polyarteritis nodosa [PAN], granulomatosis with polyangiitis [Wegnener's] [GPA], microscopic polyangiitis [MPA], or eosinophilic GPA [Churg‐Strauss] [EGPA]). Methods: A multicenter, open‐label, randomized controlled trial comprising patients ≥65 years old and newly diagnosed as having SNV was conducted. The experimental treatment consisted of corticosteroids for ∼9 months and a maximum of six 500‐mg fixed‐dose intravenous (IV) CYC pulses, every 2–3 weeks, then maintenance azathioprine or methotrexate. The control treatment included ∼26 months of corticosteroids for all patients, combined with 500 mg/m 2 IV CYC pulses, every 2–3 weeks until remission, then maintenance for all patients with GPA or MPA and for those with EGPA or PAN with a Five‐Factors Score (FFS) of ≥1. Randomization used a 1:1 ratio computer‐generated list and was performed centrally with sealed opaque envelopes. The primary outcome measure was ≥1 serious adverse event (SAE) occurring within 3 years of followup. Secondary outcome measures included remission and relapse rates. Results: Among the 108 patients randomized, 4 were excluded (early consent withdrawal or protocol violation). Mean ± SD age at diagnosis was 75.2 ± 6.3 years. Analysis at 3 years included 53 patients (21 GPA, 21 MPA, 8 EGPA, and 3 PAN) in the experimental arm and 51 patients (15 GPA, 23 MPA, 6 EGPA, and 7 PAN) in the conventional arm. In total, 32 (60%) versus 40 (78%) had ≥1 SAE ( P = 0.04), most frequently infections; 6 (11%) versus 7 (14%) failed to achieve remission ( P = 0.71); 9 (17%) versus 12 (24%) died ( P = 0.41); and 20 (44%) of 45 versus 12 (29%) of 41 survivors in remission experienced a relapse ( P = 0.15). Conclusion: For older SNV patients, an induction regimen limiting corticosteroid exposure and with fixed low‐dose IV CYC pulses reduces SAEs in comparison to conventional therapy, and does not affect the remission rate. Three‐year relapse rates remain high for both arms.